Hf isotopes in detrital and inherited zircons of the Pilbara Craton provide no evidence for Hadean continents - Kemp, A.; Hickman, A.; Kirkland, Chris; Vervoort, J. (Elsevier, 2015)
Predictions of large volumes of stabilized continental crust by the early Archaean stand in stark contrast to the actual amount of pre-3.5. Ga rocks presently exposed on Earth's surface. The Pilbara Craton of Western Australia, one of the best preserved Paleoarchean crustal blocks on Earth, is believed to have developed on a cryptic, possibly =3.8. Ga continental basement. If substantiated, this could support the notion of a widespread and enduring Hadean (ca. 4.5-4.0. Ga) felsic-intermediate crust. To test this, and to elucidate the earliest evolution of the Pilbara Craton, we report Hf isotope data from previously dated detrital zircon grains, and inherited zircon crystals hosted by granitic gneisses, the crystallization ages (3.80-3.55. Ga) of which substantially exceed those of the oldest exposed igneous rocks of the craton (~3.52. Ga). The Hf isotope compositions of the ancient zircons analyzed in this study are consistent with most of the earliest components of the Pilbara Craton being extracted from near chondritic mantle between ~3.7 and 3.6. Ga, with little or no input from significantly older crust. These new data suggest either that the Pilbara Craton developed remote from the isotopic influence of the putative Eoarchean to Hadean continental masses, or that the stabilized volumes of the earliest continents have been overestimated. The latter scenario would be consistent with the extreme scarcity of >3.9. Ga rocks and minerals, and the dominantly chondritic Hf isotope composition of the oldest continental rocks in Earth's most ancient Archaean cratons.